2021
DOI: 10.1007/s10856-021-06551-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention the formation of biofilm on orthopedic implants by melittin thin layer on chitosan/bioactive glass/vancomycin coatings

Abstract: Methicillin-resistant and Vancomycin-resistant Staphylococcus aureus bacteria (MRSA and VRSA, respectively) can seriously jeopardizes bone implants. This research aimed to examine the potential synergistic effects of Melittin and vancomycin in preventing MRSA and VRSA associated bone implant infections. Chitosan/bioactive glass nanoparticles/vancomycin composites were coated on hydrothermally etched titanium substrates by casting method. The composite coatings were coated by Melittin through drop casting techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Ideal bioactive coatings have the following properties: osteoinductivity, osteoconductivity [ 4 ], biocompatibility, an anti-inflammatory response [ 16 ], antimicrobial activity [ 17 , 18 ], corrosion mitigation, as well as suitable mechanical properties [ 19 ]. They can be composed of bioactive materials; various polymers [ 20 ], hydroxyapatite (HA) [ 21 ], calcium phosphate (CaP), titania nanotubes (TNTs) [ 22 ], carbon nanomaterials [ 23 ], etc. ; they can also contain active substances that are released from their structure into the local environment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideal bioactive coatings have the following properties: osteoinductivity, osteoconductivity [ 4 ], biocompatibility, an anti-inflammatory response [ 16 ], antimicrobial activity [ 17 , 18 ], corrosion mitigation, as well as suitable mechanical properties [ 19 ]. They can be composed of bioactive materials; various polymers [ 20 ], hydroxyapatite (HA) [ 21 ], calcium phosphate (CaP), titania nanotubes (TNTs) [ 22 ], carbon nanomaterials [ 23 ], etc. ; they can also contain active substances that are released from their structure into the local environment [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can be composed of bioactive materials; various polymers [ 20 ], hydroxyapatite (HA) [ 21 ], calcium phosphate (CaP), titania nanotubes (TNTs) [ 22 ], carbon nanomaterials [ 23 ], etc. ; they can also contain active substances that are released from their structure into the local environment [ 20 ]. Accordingly, the incorporation of anti-inflammatory drugs, such as nonsteroidal anti-inflammatory drugs (NSAIDs), can greatly reduce postoperative inflammation, as well as improving the osteointegration of the implant by promoting osteoblast proliferation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…As Nancy et al concluded, one layer is used as a storage space for vancomycin, and the other layer is a “switch” that controls the release of drugs; a schematic representation of the step-by-step process involved in fabricating single- or double-layer coatings is shown in Figure 3 F [ 58 ]. This technique was similarly used in the reports of Ionita et al [ 65 ] and Zarghami et al [ 66 ]. At present, the most important problem is how to control the stability of the mechanical properties of each film in the LbL technology.…”
Section: Antibacterial Effectsmentioning
confidence: 99%
“…Vancomycin can also be loaded onto CS to prepare surface coating for orthopedic implants with good bactericidal effect, according to Zarghami et al [51]. They prepared CS/bioactive glass/vancomycin solutions that were drop-cast over biomedical grade Ti foil with dimensions of 5 mm × 5 mm × 0.7 mm, then dried under enclosed conditions for 24 h. Finally, melittin solution was drop-cast over the coatings and dried at ambient temperature for 3 h. They assessed the cell proliferation, alkaline phosphatase (ALP) activity, and DNA content by culturing preosteoblast MC3T3-E1 cell line and examined the antimicrobial activity against MRSA and vancomycin-resistant S. aureus (VRSA) strains isolated from burn wounds of two patients.…”
Section: Vancomycinmentioning
confidence: 99%